The use of qualitative indicators for performance measurement in manufacturing control systems - Leitão, Paulo (2010)
New manufacturing control paradigms are being developed to improve the ability of enterprises to respond to change. However, there are no agreed definitions and methodologies for the evaluation and comparison of achievements of different manufacturing control systems approaches, making also difficult the communication and cooperation between manufacturing control systems developers. In this paper some qualitative performance indicators are identified and defined - re-configurability, robustness and agility - and methodologies for their evaluation are suggested.